No evidence of congenital varicella zoster virus infection assessed through dried blood spot in children with autism spectrum disorders. (July 2017) - Gentile, Ivan; Zappulo, Emanuela; Riccio, Maria Pia; Binda, Sandro; Limauro, Raffaele; Scuccimarra, Goffredo; Borgia, Guglielmo; Bravaccio, Carmela
Aim: Several authors have hypothesized an association between congenital viral infections and the onset of autism spectrum disorders (ASD). We aimed to assess the prevalence of congenital varicella zoster virus (VZV) infection in patients with ASD.Patients & methods: Congenital infection by VZV was evaluated in a cohort of 38 children with ASD and in 44 healthy controls. PCR for VZV-DNA performed on dried blood spots collected at birth.Results & conclusion: No VZV infection was detected in both groups. With the limitation of the small sample size of this study, the results are not in favor of a role of VZV in the etiology of ASD.